Application and effect mechanism of electrical nerve stimulation modulation technology in rehabilitation therapy following spinal cord injury - LIU Wenhui; SUN Wenting; HU Naichong; LI Yanpi; ZHAO Jingjun (康复学报)
Spinal cord injury （SCI） is a significant neurological condition that frequently results in substantial impairment of motor，sensory，and autonomic functions in patients. The use of neuromodulation electrical stimulation technology in the rehabilitation of SCI has demonstrated considerable promise. This study presents a review of the utilization of electrical nerve stimulation modulation techniques in post-SCI rehabilitation，along with a discussion of the potential mechanisms of action. The article examines the use of invasive techniques，including spinal cord electrical stimulation （SCS） and deep brain stimulation （DBS），and non-invasive techniques，such as peripheral nerve stimulation （PNS） and transcranial direct current stimulation （tDCS），in the context of post-SCI rehabilitation. The mechanism of action of the electrical nerve stimulation modulation technique for SCI may be related to modulating neural excitability，thus promoting the reconstruction of neural circuits and facilitating the cascade inflammatory response. Additionally，the technique has been observed to modulate synaptic plasticity，which may contribute to the regeneration and repair of nerve tissue. Neuroelectrical stimulation modulation technology has demonstrated the capacity to enhance motor and autonomic functions in individuals with SCI to a certain extent. However，it has not yet achieved the objective of promptly furnishing the optimal personalized treatment plan for the diverse spectrum of SCI. The specific stimulation frequency，intensity，duration，and waveform parameters for different segments of SCI have yet to attain a unified consensus. The subsequent study should undertake a continuous analysis of the efficacy and specific mechanisms of different interventions on neurological dysfunction following spinal cord injury in different segments. Furthermore，it should adopt a multimodal and individualized modulation scheme. Furthermore，the fundamental principles governing the use of electrical signals for the restoration of motor and sensory functions following SCI should be investigated，and a consensus should be reached by experts on the application of neuroelectrical stimulation and modulation technology in accordance with the specific type of spinal cord injury，age，and gender of the patient. It as a reference point for the application of neuroelectrical stimulation and modulation technology in the rehabilitation of SCI patients.